The use of artificial intelligence to improve EFL students' writing skill - Pratama, Rizky Mirani Desi; Hastuti, Dwi Puji (English Learning Innovation, 2024)
This research aims to analyze the use of artificial intelligence platforms that can be used to convey writing subjects. This research used a mixed-method design that combines quantitative and qualitative approaches. This research aims to test the effectiveness of AI in teaching writing involving 30 high school students around the Kalideres RPTRA as samples. Quantitative data is obtained through pre-tests and, post-tests and surveys to measure English writing skills and students' perceptions of using AI in learning writing. Qualitative data was obtained through interviews. The findings of this research show that Artificial Intelligence technology can used as a medium in developing English language learning for students, especially writing skills. This research applies AI platforms, namely Gencraft and ChatGPT. The research results show an increase in writing skills after using AI. These findings support that using AI is effective in learning English, especially writing skills. The data analysis results show that the output Sig = 0.00 means that the pre-test and post-test averages differ. The application of Gencraft and ChatGPT media is effective in improving student's writing skills. Learning effectiveness with Gencraft and ChatGPT media can also be seen from the average pre-test score of 71,47 and post-test of 46,81, which shows that learning outcomes have increased. Observations made during the learning process using Gencraft and ChatGPT media revealed that the average student's writing ability was in a good category and was improving, as evidenced by the students' work in writing descriptive texts.